Implicit racial bias and epistemic pessimism. (17th February 2017) - Lassiter, Charles; Ballantyne, Nathan
Abstract: Implicit bias results from living in a society structured by race. Tamar Gendler has drawn attention to several epistemic costs of implicit bias and concludes that paying some costs is unavoidable. In this paper, we reconstruct Gendler's argument and argue that the epistemic costs she highlights can be avoided. Though epistemic agents encode discriminatory information from the environment, not all encoded information is activated. Agents can construct local epistemic environments that do not activate biasing representations, effectively avoiding the consequences of activation. We conclude that changing our local environments provides a way to avoid paying implicit bias's epistemic costs.